2018
DOI: 10.15585/mmwr.mm6733a3
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Patterns in Unintentional and Undetermined Drug-Involved and Opioid-Involved Overdose Deaths — United States, 2007–2012

Abstract: The opioid epidemic affects multiple segments of the U.S. population (1). Occupational patterns might be critical to understanding the epidemic. Opioids are often prescribed for specific types of work-related injuries, which vary by occupation* (2). CDC used mortality data from the National Occupational Mortality Surveillance (NOMS) system to examine unintentional or undetermined drug overdose mortality within 26 occupation groups. This study included data from the 21 U.S. states participating in NOMS during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 4 publications
2
45
0
Order By: Relevance
“…Table 3 The higher odds of prescribed opioid use among injured construction workers could be one of the major factors underlying the higher prevalence of opioid use and the higher rate of opioid-related overdose deaths in construction occupations that have been previously reported. 16,17,32 Construction is one of the industries with high risks of injury at worksites. The rates of work-related fatal and nonfatal injuries are consistently higher than most industry sectors and the overall workforce in the United States.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 The higher odds of prescribed opioid use among injured construction workers could be one of the major factors underlying the higher prevalence of opioid use and the higher rate of opioid-related overdose deaths in construction occupations that have been previously reported. 16,17,32 Construction is one of the industries with high risks of injury at worksites. The rates of work-related fatal and nonfatal injuries are consistently higher than most industry sectors and the overall workforce in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…14 Studies also found that construction workers were more likely to use opioids and die of opioid-related overdoses than workers in other industries. [15][16][17][18][19][20] Furthermore, workplace overdose fatalities in the construction industry increased ninefold from 2011 to 2018, double the increase in all industries combined during the same period. 21 In response to this opioid crisis in the workplace, a great number of studies have been done through various approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 41 deaths 19 were assigned code X44 (Accidental poisoning by and exposure to other and unspecified drugs, medicaments and biological substances), 16 were assigned code X42 (accidental poisoning by and exposure to narcotics and psychodysleptics [hallucinogens], not elsewhere classified) and three were assigned code X45 (Accidental poisoning by and exposure to alcohol). While it is not possible for us to establish with certainty what this increase may be associated with, it is likely an early effect of the opioid epidemic that is raging through the US, including the construction trades . A recent study of mortality from this cause in Massachusetts found that construction trades workers accounted for the largest number of deaths from opioid poisoning, totaling 26.8% of all such deaths, for a rate of death more than six times higher than all occupations combined.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot be certain what medications were prescribed for pain, it is highly likely that most of these prescriptions were for opioids. The disproportionately high rates of use and overdose of opioids seen in the construction industry likely rise from several causes, including high rates of injury and subsequent medical care among construction workers, the intermittent nature of construction work, and the lack of paid sick leave: the need to return to work soon after an injury or to work while in pain may contribute to high rates of opioid use among construction workers and workers in other occupations with lower availability of paid sick leave and lower job security…”
Section: Discussionmentioning
confidence: 99%
“…The use of pain medication is relevant to employers due to increasing evidence that construction workers are at a uniquely high risk of opioid use and overdose, and to increase recognition by the construction industry of the need for improved prevention of opioid use disorder. Recent studies have shown that construction workers and miners are more likely than workers in other industries to be prescribed opioids and to receive prescriptions for longer periods of time, and that construction workers and miners are at markedly high risk of opioid overdose fatalities (up to six times the rate of overdose fatalities compared to the general workforce in Massachusetts) . There is growing awareness and calls for action among construction employers and safety professionals for action to reduce the high personal and economic costs of opioid use in this industry…”
Section: Introductionmentioning
confidence: 99%